ANALISIS BUTIR SOAL PENILAIAN TENGAH SEMESTER MATA PELAJARAN PPKn KELAS VII DI SMP MUHAMMADIYAH 7 YOGYAKARTA - Angga Dian Rotama; Tri Wahyu Budiutomo; Ahmad Nasir Ari Bowo (Academy of Education Journal, 2020)
There are 24 out of 40 (60%) items that are classified as easy, 15 out of 40 (37.5%) items that are classified as moderate, and 1 of 40 (2.5%) items that are classified as difficult. The results showed that most of the end of semester PPKn lessons had a distinguishing feature of 31 out of 40 (77.5%) items having high differentiation, 9 out of 40 (22.5%) were medium, and none had Low power difference. Mid-term assessment questions PPKn have a complete check that requires 33 of the 40 (82.5%) choices have distractors working, and 7 out of 40 (17.5%) options have distractors who don't work. This must be fixed, but still waiting for problems that have a fraud that does not need to be repaired by using the deception used.